2013
DOI: 10.1152/jn.00921.2012
|View full text |Cite
|
Sign up to set email alerts
|

Altered PKA modulation in the Nav1.1 epilepsy variant I1656M

Abstract: lepsy with febrile seizures plus (GEFS ϩ ) is an inherited epilepsy that can result from mutations in at least four ion channel subunits. The majority of the known GEFS ϩ mutations have been identified in SCN1A, the gene encoding Na v 1.1 ␣-subunit. Protein kinases as critical modulators of sodium channels have been closely related to the genesis of epilepsy. However, little is known about how protein kinases affect the GEFS ϩ mutant sodium channel. To gain insight into the protein kinases effect on channel pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 51 publications
1
8
0
Order By: Relevance
“…Much less is known about the regulation of Nav1.1 channels, although, earlier recombinant studies and more recent proteomic work has identified putative phosphorylation sites which often overlap with sites identified for Nav1.2 channels (Smith and Goldin, 1998; Berendt et al, 2010). Interestingly, forskolin activation of PKA causes a hyperpolarizing shift in both the activation and inactivation curves for recombinant Nav1.1 (Liu and Zheng, 2013) as observed in the present study on cerebellar SCs. An identical gating shift is observed in hippocampal CA1 pyramidal cells, probably mediated by Nav1.2 channels, that is triggered by NMDA receptor activation and the activity of CaM kinase II (Xu et al, 2005).…”
Section: Discussionsupporting
confidence: 81%
“…Much less is known about the regulation of Nav1.1 channels, although, earlier recombinant studies and more recent proteomic work has identified putative phosphorylation sites which often overlap with sites identified for Nav1.2 channels (Smith and Goldin, 1998; Berendt et al, 2010). Interestingly, forskolin activation of PKA causes a hyperpolarizing shift in both the activation and inactivation curves for recombinant Nav1.1 (Liu and Zheng, 2013) as observed in the present study on cerebellar SCs. An identical gating shift is observed in hippocampal CA1 pyramidal cells, probably mediated by Nav1.2 channels, that is triggered by NMDA receptor activation and the activity of CaM kinase II (Xu et al, 2005).…”
Section: Discussionsupporting
confidence: 81%
“…This suggests that both the function and expression of Na v 1.2 are modified by PKA. Since these early studies, other groups have reported similar decreases in Na v 1.1, Na v 1.6, and Na v 1.7 in different cell expression systems and intact cells ( Gershon et al, 1992 ; Cantrell et al, 1997 ; Smith and Goldin, 1998 ; Zhou et al, 2000 ; Vijayaragavan et al, 2004a ; Chen et al, 2008 ; Liu and Zheng, 2013 ). The phosphorylation sites of Na v 1.2 by PKA were mostly investigated using traditional biochemical approaches ( Murphy et al, 1993 ; Smith and Goldin, 1996 ; Cantrell et al, 1997 ).…”
Section: Protein Kinasesmentioning
confidence: 69%
“…Increasing cytosolic cyclic AMP concentration results in activation of protein kinase A (PKA), which we found in the nodal region, and other intracellular pathways [32,33]. Through kinase activation, CGRP could regulate ion channels essential for nerve signal propagation [34][35][36] and contribute to mechanisms of neural sensitization and/or increased intensity of pain transmission in migraine. Nodes of Ranvier are complex, highly organized structures in which the central, unmyelinated portion of the node itself is flanked by paranodal and juxtaparanodal regions [15].…”
Section: Possible Mechanism Of Sensitizationmentioning
confidence: 84%